Effective adsorption of crystal violet onto aromatic polyimides: Kinetics and isotherm studies. (October 2022) - Loganathan, M.; Raj, Arya S.; Murugesan, A.; Kumar, P. Senthil
Abstract: The motive of this work is to synthesis aromatic polyimides by a two-step poly condensation process and the prepared aromatic polyamides (APIs) is been used as an effective functionalized adsorbent for the removal of carcinogenic crystal violet (CV) from aqueous medium. The adsorption efficiency of the APIs was enhanced by incorporation different functional moieties (varying aromatic dianhydrides with - O -, –(CF3 )2 –, –(CH3 )2 –) in the polymer structure. The initial and final concentration of CV was measured using UV–Vis spectrometer. The adsorption process was optimized by varying the parameters such as the effect of solution pH, contact time, initial dye concentration, and adsorbent dosage. Kinetics and isotherms of the adsorption system were appraised using data obtained from effect of contact time and initial dye concentration with corresponding empirical modelling techniques respectively. The evaluated results of the adsorption kinetic studies confirmed that the adsorption of API onto CV is followed a pseudo-second-order kinetic model. The adsorption behaviour and their interactions between APIs and CV are well established. The experimental results of this research output could be confirmed that APIs is a very effective adsorbent for the removal of cationic dye from aqueous. Graphical abstract: Image 1 Highlights: Aromatic polyimides are an effective adsorbent which is been produced by two-step polycondenzation technique. APIs are employed to adsorb of CV dye from polluted water sources. The CV adsorption onto APIs follows pseudo-Second-order kinetics, which is justified by kinetic data. This research revealed that the highest adsorption capacity of APIs-1-CV is 287.71 mg/g and that of APIs-2-CV is 303.03 mg/g. APIs proved to be a superior adsorbent for cationic dye removal.